Nasopharyngeal bacterial carriage and antimicrobial resistance in underfive children with community acquired pneumonia - Cissy B. Kartasasmita; Heda Melinda Duddy; Sunaryati Sudigdoadi; Dwi Agustian; Ina Setiowati; Tri Hanggono Ahmad; Ramdan Panigoro (Indonesian Pediatric Society, 2001)
Lung puncture is the best way to determine the etiology of pneumonia since it yields the highest rate of positive cultures. However, this procedure is difficult, especially for a study in the community. According to WHO, isolates to be tested for antimicrobial resistance in the community should be obtained from nasopharyngeal (NP) swabs. Previous studies support the use of NP isolates to determine antimicrobial resistance patterns of isolates from children with pneumonia. The aim of our study was to know the bacterial patterns of the nasopharynx in underfive children with community acquired pneumonia and their antimicrobial resistance. The study was carried out in 4 Primary Health Clinics in Majalaya sub-district, Bandung, Indonesia. All underfives with cough or difficult breathing and classified as having non-severe pneumonia (WHO guidelines), were included in the study. Nasopharyngeal swabs (CDC/WHO Manual) were obtained by the doctor, the swabs were placed in Amies transport medium and stored in a sterile jar before taken to the laboratory in the same day. All children were treated with co-trimoxazole. During the nine month study, 698 children with clinical signs of non-severe pneumonia were enrolled. About 25% of the nasopharyngeal specimens yielded bacterial isolates; the two most frequently found were S. pneumoniae and S. epidermidis. The antimicrobial resistance test to co-trimoxazole showed 48.2% S. pneumoniae strain had full resistance and 32.7% showed intermediate resistance to co-trimoxazole. This result is almost similar to other studies from Asian countries. It seems that H. influenzae is not a problem in the study area; however, further studies are needed.